FORMING A HEALTHY LIFESTYLE THROUGH GYMNASTIC EXERCISES - Hayitov , Jumaqul Negmatovich (Educational Research in Universal Sciences, 2023)
This article describes how to build a healthy lifestyle through gymnastics and its important role in human life.